Regulation of polar morphogenesis in Caulobacter crescentus. - Fukuda, A (1981)
Deoxyribonucleic acid (DNA) phage phi CbK-resistant nonmotile mutants of Caulobacter crescentus CB15 were examined for their formation of polar surface structures (a stalk, a single flagellum, pili, and DNA phage receptors). These mutants were devoid of pili and DNA phage receptors and simultaneously defective either in both stalk formation and flagellar activity (stalk-defective type) or in the formation of normal flagella (flagella-defective type). DNA phage phi Cr30-mediated transductions revealed that stalk-defective mutants were of a single genetic type, whereas flagella-defective mutants were grouped into two different genetic types, I and II. To investigate how membrane proteins change in the above morphology mutants, cell envelopes pulse-labeled with L-[35S]methionine were analyzed by two-dimensional gel electrophoresis. No gross change of membrane proteins was observed in the stalk-defective mutant CB15 pdr-803, except a 49,000-molecular-weight (49K) protein which was found reduced. However, a 27K, two 28.5K, and a 70.5K protein were missing from the membrane of the flagella-defective type I mutant CB15 pdr-813. These proteins are most likely to be flagella-related protein, flagellins A and B, and hook protein, respectively. In another flagella-defective type II mutant, CB15 pdr-816, the 27K and two 28.5K proteins were similarly absent but the 70.5K protein was consistently present in the membrane. The synthesis of flagellin was next assayed radioimmunologically in the above 35S-labeled mutants. Stalk-defective CB15 pdr-803 synthesized flagellin normally, compared to the wild-type strain. Flagellins A (26K) and B (28K) formed multiple spots in isoelectric focusing. A 29K protein was also detected in the flagellin-specific radioactivity from the cytoplasm. Flagella-defective type I CB15 pdr-813 synthesized flagellin only at a basal level. Thus transcription or translation of flagellin appeared to be repressed in this mutant. Another flagella-defective type II strain, CB15 pdr-816, however, synthesized flagellin at an apparently enhanced rate compared with the wild type. Flagellin synthesized in CB15 pdr-816 was flagellin A and a smaller 22K flagellin. Flagellin B was not synthesized in the mutant. It then follows that flagellin B is not a precursor of flagellin A and the 22K flagellin. Flagella-defective type II CB15 pdr-816, without flagellin B, formed a stub structure with a hook attached to one end instead of normal flagella. In the wild-type membrane, flagellin B was the major flagellin, whereas flagellin A was major in the cytoplasm and the flagellar filament. It is suggested from these results that flagellin B is important in the assembly of normal flagella.